An improved Dynamic Voltage Restorer for power quality improvement. (November 2016) - Chandrasekaran, K.; Ramachandaramurthy, V.K.
Highlights: Developed a Dynamic Voltage Restorer (DVR) model in PSCAD/EMTDC platform. Better performance in terms of fast speed and low total harmonic distortion (THD). New improved Synchronous Reference Rotating Frame (SRRF). Improved RLC interface filter to eliminate voltage harmonics and switching harmonics. Completely compensate voltage imperfections under different operation conditions. Abstract: The capacity of the voltage source inverter (VSI) and the values for the link filter connected between the injection transformer and the inverter play a crucial in the design of the DVR. In this research paper, new Dynamic Voltage Restorer (DVR) topology has been proposed. The capacity of the voltage source inverter (VSI) and values of the link filter is small that will improve the compensation capabilities for voltage harmonic, swell and voltage sag mitigation under various fault conditions. The new RLC filter is able to eliminate the switching harmonics. The capacity of the dc supply voltage is reduced when the value of inductance is small. The new DVR topology has high efficiency and the ability to improve the quality of voltage. An outline architecture of the RLC filter parameters for the specific model has been presented. The new DVR topology is modeled and simulated using the PSCAD/EMTDC. The control scheme has good control dynamics with minimum transient current overshoot. The simulation results under transient performance are good.